EFFECT OF WORK ENGAGEMENT AND KNOWLEDGE MANAGEMENT ON WORK PRODUCTIVITY - Nazifah Husainah; Maswanto Maswanto (Jurnal Ekonomi Trisakti, 2022)
Work Engagement and Knowledge Management on Work Productivity". The research method used in this study is associative with a sample of 83 respondents, and the data analysis method used is with test t and test F. Based on the study results in the following results: There is an influence between work engagement and work productivity. There is the influence of knowledge management on work productivity partially. There is an influence jointly between work involvement and knowledge management on work productivity. Simultaneously 72.9% and the remaining 27.1% are affected by other variables. The implication of this research is work involvement. In this case, the Company is expected to pay more attention to providing feedback on employee work results so that employees are always motivated to do their work well. The company needs to provide clear and challenging tasks and targets